Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Intrinsik dan Motivasi Ekstrinsik terhadap Kinerja Karyawan PT Bank Rakyat Indonesia (Persero) KC Kendal - Hernanda Diva Auliya; Suhana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to find out and analyze the extent to which transformational leadership style variables, intrinsic motivation and extrinsic motivation affect employee performance. This research object is PT Bank Rakyat Indonesia (Persero) KC Kendal with a sample of 100 permanent employees. Sample selection using saturated sampling. The method used is a quantitative method by collecting data using a questionnaire and distributed by gform with a likert scale as a measurement tool. The types of data used are primary data and secondary data. Data processing and testing using the SPSS version 26 program. The instrument tests used are validity tests and reliability tests. The analysis techniques used include multiple linear regression analysis, f tests, coefficients of determination, and hypothesis tests (tests). The findings in this study show that Transformational leadership style and intrinsic motivation have a positive and significant effect on employee performance. In addition, extrinsic motivation also plays a role in influencing employee performance.